A darkness more than night [compact disc, unabridged] - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series., 2001)
When a slew of slayings leave the LAPD puzzled, they call on retired FBI agent turned best selling author Terry McCaleb for help. McCaleb, known for his ability to profile serial killers, is shocked when his methods indicate that his former partner, homicide detective Harry Bosch, could very well be the killer.